Kesukubangsaan dan Primordialitas: Program Ayam di Desa Mwapi, Timika, Irian Jaya - Parsudi Suparlan (Antropologi Indonesia, 1997)
In this article, Suparlan uses both concepts of ethnicity and primordialism in explaining the failure of Poultry Farming Assistance Program carried out by the local office of the general of Animal Housebandry in Mwapi Villlage, Irian Jaya. Among the Komoro's who live in this village are divided into two clans: Muare and Pigapu. Their culture is called Ndaitita which mainly based on egalitarianism. They do not have a formal social stratification. Each person perceived as atomistic individual. Concepts of state and larger societies do not exist in Komoro's culture. Their social relations base on family and clan. When the head of Mwapi villages had task to coordinate the chicken program, he only recruited the persons from his clan: Muare. According to Suparlan, the heads start his ethnicities in forming make this group. But the programs started to ruin when the group had to work together. Komoro' peoples are very individualistic. So, the programs had failure. To cover up these problems, Chief starts his primordialism as the core beliefs.